ETIKA KEPROFESIAN GURU DALAM PEMBELAJARAN ANAK CEREBRAL PALSY DI SEKOLAH LUAR BIASA (STUDI LITERATUR DAN OBSERVASI DI SLB N 1 BANTUL) - Widyawati, Gadiza; Nivebriyanti, Chatarina; Amelia, Putri; Anugerah Dahus, Yehezkiel; Brian Ayu, Bilqis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the importance of professional teacher ethics in guiding and teaching children with special needs (Cerebral Palsy) in Special Schools. Professional teachers have the responsibility to provide fair, patient, and respectful educational services that honor the differences of each student. In the learning process, teachers do not only act as instructors, but also as mentors who are able to create a safe, comfortable learning environment that supports the development of students with special needs. Moreover, teachers must also be able to provide learning that suits the needs of children, especially children with cerebral palsy. Professional teacher ethics is reflected through the attitude of respecting students' rights, teachers who are able to communicate well with their students, as well as collaborating with parents in monitoring the growth and development of children and professionals such as therapists and others. The application of good ethics can help improve learning motivation, self-confidence, as well as the academic and social development of students. Thus, professional teacher ethics not only affects the learning success of students, but also contributes to the creation of an educational environment that respects the diverse learning needs of children and upholds humanitarian values.